Fecal Microbiota Transplantation Effectively Cures a Patient With Severe Bleeding Immune Checkpoint Inhibitor-Associated Colitis and a Short Review - Chen, Minmin; Liu, Mengyuan; Li, Chenyan; Peng, Shiqiao; Li, Yiling; Xu, Xiuying; Sun, Mingjun; Sun, Xuren (Frontiers in Oncology, 2022)
Immune checkpoint inhibitors (ICIs) have opened up a new way for tumor therapy but simultaneously led to the occurrence of immune-related adverse events. We report a case of successful treatment of PD-1 inhibitor-associated colitis with fecal microbiota transplantation (FMT). The patient was a palatal malignant melanoma who developed diarrhea and hematochezia accompanied by fever, gastrointestinal bleeding, and infection after the third treatment with PD-1 (Toripalimab). The patient received general treatment unsuccessful, corticosteroid therapy after initial success but rapid loss of response, and finally successful treatment after fecal microbiota transplantation.